Arts and Crafts Pioneers: The Hobby Horse Men and Their Century Guild. - Waithe, Marcus (Victorian Studies)
"Arts and Crafts Pioneers: The Hobby Horse Men and Their Century Guild" by Stuart Evans and Jean Liddiard is an art book that explores the development of the Century Guild, an artists' and architects' collective founded on Ruskinian principles. The book focuses on the biographies and artistic styles of the guild's members, highlighting their influence on the Arts and Crafts movement and their connections to other artistic circles, such as the Rhymers' Club and the Pre-Raphaelites. The authors argue that the Century Guild's impact was more complex and diverse than previously thought, challenging the notion of a linear progression of art movements.